2021
DOI: 10.1001/jamaoncol.2021.1499
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Mass Index, Central Obesity, and Body Composition With Mortality Among Black Breast Cancer Survivors

Abstract: IMPORTANCE Obesity disproportionately affects Black women, who also have a higher risk of death after a breast cancer diagnosis compared with women of other racial/ethnic groups. However, few studies have evaluated the association of measures of adiposity with mortality among Black breast cancer survivors.OBJECTIVE To assess the association of measures of adiposity with survival after a breast cancer diagnosis among Black women. DESIGN, SETTING, AND PARTICIPANTSThis prospective population-based cohort study co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 38 publications
1
74
0
Order By: Relevance
“…30,31 Our study result was consistent with previous study that African Americans had a higher risk of death after a breast cancer diagnosis compared with women of other racial groups. 32 Excluding the therapeutic factors, AJCC 6th edition N stage contributes the most to 1104 the final risk score (Figure 2), with HRs increasing with ascending N stages. The significant contribution of N stage to this nomogram strongly suggests that certain subsets of breast cancer may have an enhanced propensity to metastasize, exhibiting a worse prognosis even when the primary lesion is very small.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Our study result was consistent with previous study that African Americans had a higher risk of death after a breast cancer diagnosis compared with women of other racial groups. 32 Excluding the therapeutic factors, AJCC 6th edition N stage contributes the most to 1104 the final risk score (Figure 2), with HRs increasing with ascending N stages. The significant contribution of N stage to this nomogram strongly suggests that certain subsets of breast cancer may have an enhanced propensity to metastasize, exhibiting a worse prognosis even when the primary lesion is very small.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that women who took hormones had a 26% increased risk of BC ( 9 ). And women with a higher waist-to-hip ratio had a 68% increased risk of dying from BC ( 10 ). Young age is associated with the risk of distant metastasis of BC, but its effect on survival remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of the fat mass on cancer mortality can vary based on the cancer type ( 40 ). For example, higher adiposity was associated with higher all-cause and cancer-specific mortality in breast cancer patients ( 45 ). In the present study, the favorable impact of the FAIN on patient survival was also attenuated in breast cancer patients ( Table 4 ), which might suggest that the FAIN would be of limited use in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%